A Limelight on the Affirmative Impact of Kriyakalpas Apropos of the Sense Organs and its Management in the Epidemiological Diseases- An Overview - Rengapadmini B; Balasubramaniam S; Anita Patel (International Journal of Ayurveda and Pharma Research, 2022)
Ever since the days of yore, the infectious pandemics of natural or man-made origin greatly influence sensory health. Hence proper cleansing and rejuvenating of the sensory organs is needed in protecting us from the rising pandemics. This article is an overview of the Comprehensive analysis of Shalakya tantra references from the Brihat trayee and Sharangadhara Samhita regarding the etiopathogenesis of Janapadhodhwamsa affecting the Uttamangam, its clinical features, its management through kriyakalpam like Nasyam, Dhumapaana, Gandusa, Kavala, Prathisaaranavidhi, Lepa, Murdhinitailam, Karnapurana, Netra prasadana kalpas and its mode of action in strengthening and protecting the sensory perceptions from the damage of non-biological physical agents. Henceforth the review concludes that the Kriyakalpam acts as fundamental habitual preventive practice and serves as the foundation of treatment methods for a cascade of conditions arising as complications to reduce mortality and morbidity.